A green bio-inspired chelating design for improving the electrical conductivity of flexible biopolymer-based composites. (20th February 2021) - Li, Kuang; Jin, Shicun; Li, Xiaona; Shi, Sheldon Q.; Li, Jianzhang
Abstract: Petroleum-based electronic components bring great potential hazards and risks to public health and environment, and it is still challenging to develop conductive biopolymer materials with high mechanical properties. Herein, we develop an eco-friendly and sustainable strategy for the preparation of soy protein (SP)-based nanocomposite films by the introduction of cellulose nanofibril template-directed pyrrole (CNF@Py) hybrids and a phytic acid (PA) system. The CNF@Py hybrids are prepared and well-dispersed by in-situ oxidative polymerization of the Py monomers on the bio-template of CNF, which are chelating-mediated through the PA system. The synthetic PA/CNF@Py hybrids not only endow SP matrix with superior electrical conductivity, but also serve as active chelating sites to enhance the multiple cross-linking networks in the biopolymer material. This SP-based nanocomposite film has high mechanical properties, tensile strength of up to 13.69 MPa, and toughness of 13.93 MJ/m 3, which is far superior to that of most SP-based composites. The electrical conductivity of the composite film reached 8.15 × 10 −6 s/m. In addition, this nanocomposite film exhibited favorable water absorption characteristics and thermal stability. This research provides valuable guidance for the design of high-performance protein-based conductive materials, and opens up the possibility for various applications in multifunctional electronic devices. Graphical abstract: Image 1 Highlights: This conductive soy protein-based film is eco-friendly and sustainable. CNF serves as a bio-template for in-situ oxidative polymerization of pyrrole. Phytic acid acts as a chelating site to enhance the cross-linking network. The strength and toughness of composite film increase by 353.3% and 792.9%. The electrical conductivity of the composite film reached 8.15 × 10 −6 s/m.